Pengaruh Digital Marketing dan Kualitas Pelayanan Terhadap Keputusan Pembelian di Indomaret Surabaya - Nurya Rizkiyani; Iswati Iswati; Emilia Pranata (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2024)
This research seeks to provide a deeper understanding of the "Effect of Digital Marketing and Service Quality on Purchasing Decisions at Indomaret Surabaya City" related to the main issues discussed by the relationship between digital marketing and service quality on purchasing decisions at Indomaret Surabaya City. The background of this research is the rapid development of innovation, so that a new marketing strategy has emerged, namely digital marketing. However, not only that, service quality also plays a role in how influential it is on purchasing decisions. Proving the effect of digital maeketing and service quality on purchasing decisions at Indomaret Surabaya City is the main objective of this study. Data was collected through a quantitative survey using Google Form and processed by quantitative methods to Indomaret customers in Surabaya City, especially East Surabaya. Researchers used purposive sampling, so that researchers selected data that reflected respondents from the population obtained. After that, the data that has been collected is run with SPSS and Multiple Linear Regression for data analysis. The conclusion of this study is that there is a relationship from digital marketing and service quality on purchasing decisions.